A comparative density functional theory study of BMSF-BENZ chemisorption on Zn12O12, Al12P12 nanocages - Al-Sawaff, Zaid; Dalgic, Serap Senturk; Najim, Zaheda A.; Othman, Shatha S.; Kandemirli, Fatma (Physics and Chemistry of Solid State, 2022)
In this paper, density functional theory (DFT) study was applied to the absorption of BMSF-BENZ ((4-bromo-7-methoxy-1-(2-methoxyethyl)-5-[3 (methylsulfonyl)phenyl]methyl)-2-[4-(propane-2)) yl)phenyl]-1H-1,3-benzothiazole) used for the treatment of Osteoporosis, on the surfaces of two types of nanocages Zn12O12 and Al12P12. The results showed that the interaction of BMSF-BENZ with the nanocages was highly exothermic, indicating the high chemical adsorption of the new complexes. The adsorption energies of the ZnO nanocage were higher than those of AlP for all the active atoms investigated on the drug compound (Br, N8, N9, N58, O35, O42, and S). Topology analyses such as QTAIM and NCI/RDG indicate that the interactions between the BMSF-BENZ drug and the surface of the ZnO nanocage are more substantial than that of the AlP nanocage. The obtained results of charge, the total density of states (TDOS), and boundary molecular orbital analysis confirm a characteristic orbital hybridization upon adsorption of BMSF-BENZ, indicating the potential application of AlP as a biochemical adsorbent for BMSF-BENZ. However, ZnO nanocage is a candidate for drug delivery applications.